Protective Effect of Glycyrrhiza glabra Linn in Aniline-Induced Spleen Toxicity in Rats - Jain, Sourabh (International Journal of Pharmaceutical & Biological Archive, 2022)
Glycyrrhiza glabra (GG) is an herbal plant which has lots of medicinal properties such as antimicrobial, antioxidant, anti-inflammatory, antitussive, antidiabetic, antiviral, anticancer, antimutagenic, antiulcer, and hepatoprotective. The phytochemicals present in GG have been of immense importance in phototherapeutics. The present study was designed to evaluate the protective effects of GG on hematological and biochemical changes in aniline-induced spleen toxicity in rats. Wistar rats of either sex (200–300 g) were used in the study and each group contains six rats. Splenic toxicity was induced in rats by administration of aniline hydrochloride (AH; 100 ppm) in drinking water for a period of 30 days. Treatment groups received GG (50, 100 and 200 mg/kg/day, p. o) along with AH for 30 days. At the end of treatment period, various serum and tissue parameters were evaluated. AH-treated rats showed a significant alteration in body weight, spleen weight, feed consumption and water intake, hematological parameters (Hemoglobin, red blood cells, white blood cells, and total iron content), biochemical parameters (total iron content, total protein, lipid peroxidation, reduced glutathione, and nitric oxide), and membrane bound phosphatase (ATPase). The treatment with GG (50, 100, and 200 mg/kg/day, p. o) for 30 days along with AH showed significant recovery in aniline-induced splenic toxicity. Conclusion: The present result showed that involvement of oxidative and nitrosative stress in aniline-induced splenic toxicity and GG protects the rats from the toxicity, which might be due to its antioxidant property and the presence of different phytochemicals.